LA PROYECCIÓN DE IMÁGENES EN LAS AULAS DE BACHILLERATO EN ESPAÑA DURANTE EL PRIMER TERCIO DEL SIGLO XX - Carmen LÓPEZ SAN SEGUNDO,Beatriz GONZÁLEZ DE GARAY DOMÍNGUEZ,Francisco Javier FRUTOS ESTEBAN,Manuela CARMONA GARCÍA (Fonseca, Journal of Communication, 2023)
In the context of the research project ‘Dynamics of Educational and Scientific Renewal in Secondary School Classrooms (1900-1936): An Iberian perspective’ (HAR 2014-54073) it has been developed an empirical study using the methodology of Content Analysis. This methodology has been applied to the set of visual messages with divulgative character was projected all over the Historical High School in Spain. The results of the studies reveal relevant aspects of the role that mentioned elements of material culture had in the transformation of the science teaching in the Secondary School Classrooms in the First Third of the 20th.